1-(3-Methyl-3-Phenylcyclobutyl)-2-(Piperidin-1-yl) Ethanone Oxime - Dinçer, M.; Özdemir, Nutullah; Çukurovali, A.; Yilmaz, I.; Büyuk̈güngör, O. (Int Union Crystallography, 2006)
The asymmetric unit of the title compound, C18H 26N2O, contains two molecules. In both molecules, the oxime group has an E configuration and the piperidine ring adopts a chair conformation. Intramolecular C-H⋯O and intermolecular O-H⋯N hydrogen bonds are observed in the crystal structure. © 2006 International Union of Crystallography Printed in Great Britain - all rights reserved.